Ферорезонансні режими роботи синхронних машин - Білий, Леонід Адамович; Поліщук, Олег Степанович; Лісевич, Світлана Петрівна; Поліщук, Андрій Олегович (Національний технічний університет "Харківський політехнічний інститут", 2020)
Ілюструються широкі можливості знаходження усіх стійких і нестійких ферорезонансних режимів роботи і визначення границь зони самозбудження синхронних генераторів на основі моделі чутливості змінних стану до початкових умов. Апробація методу проведено на прикладі синхронного генератора, диференціальні рівняння якого мають нормальну форму Коші і який працює у режимі двофазного вмикання на ємність при обриві третьої фази.

It is proposed to use the method of sensitivity of variable models to the initial conditions for the calculation of ferroresonance modes of operation of saturated electric machines. Methodology. The calculation algorithms are based on Newton's iterative formula. The initial values of the variables determine the area of attraction of stable or unstable modes. Results. The results are illustrated by an example of the analysis of one of the most difficult modes of operation - two-phase switching on the capacity of a synchronous generator at the breakage of the third phase. Originality. The originality of the method is the ability to determine all the stable and unstable modes, as well as the self-excitation zone of the synchronous generator. Practical value. The method is universal and can be used to investigate resonance phenomena in any circle using steel.
Ferroresonance modes of operation of synchronous machines
Keywords: модель чутливості до початкових умов; зона стійкості; initial conditions sensitivity model; stability zone